The evolution, structure and market for birding tourism in South Africa. - Simango, Soza Sydney (My University, 2011)
The aim of this study was to define the structure, size and evolution and growth of one of the contributing markets to recent tourism growth in South Africa, bird watching tourism. Regarded as one of the fastest growing niche ecotourism markets both internationally and in South Africa, this report traces the growth patterns and outlines the organisation and structure of the sub-sector in South Africa. The report also provides an estimate of the market’s potential contribution to the tourism economy in South Africa. The findings presented in this report are based on original interviews with 12 individuals in the birding, conservation and government sector. A wide variety of documentary sources including the 2009 Kaiser Associates report on Bird watching in South Africa and the recently published report on the South African birding watching tourism industry report by the Department of Trade and Industry have also informed the findings and content of this report. Again, findings on the demand and supply elements of birding in South Africa were analysed from 68 individually collected and an online based survey conducted amongst birders and specialised birding tour operators. Amongst the major findings of the study is the fact the growth of birding tourism in South Africa is largely run by BirdLife South Africa through its 80 year old nationwide network of more than 50 community clubs or branches which mobilise and induct new birders and volunteers into bird watching. Most critical about the bird clubs are the several day, weekend and bird monitoring events and outings that are organised by the each of the clubs. It has been shown that local birders attend approximately 31 birding events and outings and spend R1415 per annum per trip excluding spend on, birding services and equipment per annum. There are between 13000 to 24000 bird watchers in South Africa and that between 8000 and 16000 international birders visit South Africa per annum (the dti, 2010). Based on these numbers, this study has shown that birding tourism industry contributes between R 809 million to R 1.668 billion per annum to South Africa’s Gross Domestic Product.